2019
DOI: 10.3389/fneur.2019.00665
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Inflammatory Microenvironment in the Human Cochlea by Perilymph Analysis: Toward Liquid Biopsy of the Cochlea

Abstract: The molecular pathomechanisms in the majority of patients suffering from acute or progressive sensorineural hearing loss cannot be determined yet. The size and the complex architecture of the cochlea make biopsy and in-depth histological analyses impossible without severe damage of the organ. Thus, histopathology correlated to inner disease is only possible after death. The establishment of a technique for perilymph sampling during cochlear implantation may enable a liquid biopsy and characterization of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 59 publications
1
34
0
2
Order By: Relevance
“…In addition, the immunological predisposition of each individual may influence the responsiveness to steroids and other antiinflammatory agents. The initial immunological status before implantation can now be detected in tiny perilymph samples with significant variations between the patients (29). In the future, it may be possible to diagnose just these constellations in which steroid injections are most likely beneficial for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the immunological predisposition of each individual may influence the responsiveness to steroids and other antiinflammatory agents. The initial immunological status before implantation can now be detected in tiny perilymph samples with significant variations between the patients (29). In the future, it may be possible to diagnose just these constellations in which steroid injections are most likely beneficial for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that in the present study, we observed that ABR thresholds were lower in implanted animals subjected to NT compared to implanted animals or those exposed to NT alone Although the precise reasons for this effect are still not known, it is possible that implanted animals actually receive less sound due to the electrode in the cochlea compared to non-implanted animals. In addition, there is a release of growth factors as well as heat shock proteins (HSP) in the inner ear following CI (Warnecke et al, 2019). Higher insulin-like growth factor binding protein 1 (IGFBP-1) levels have been observed in the perilymph of implanted individuals (Warnecke et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a release of growth factors as well as heat shock proteins (HSP) in the inner ear following CI (Warnecke et al, 2019). Higher insulin-like growth factor binding protein 1 (IGFBP-1) levels have been observed in the perilymph of implanted individuals (Warnecke et al, 2019). IGFBP1 regulates the action of IGF-1 that plays a crucial role in the embryonic and postnatal development of the cochlea (Camarero et al, 2001; Digicaylioglu et al, 2004; Bach, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A miniaturized variant of the manufacturer's instructions was used. 39 As little as 1-2 ÎŒL of the samples was diluted with sample diluent (1:20) and incubated with multiplex beads for 45 minutes, followed by two washings steps. Afterwards, a cocktail of biotinylated secondary murine antibodies was added for 30 minutes and after final washing steps, the streptavidin-PE was added.…”
Section: Cytokine Profilingmentioning
confidence: 99%